Challenges in Malay essay writing: a qualitative study among non-native speakers in primary school - Austrus, Edmund; Mahamod, Zamri; Adnan, Nor Hafizah (Intelektual Pustaka Media Utama, 2025)
This research addresses challenges faced by non-native speakers in primary school, specifically focusing on the proficiency of Malay essay writing skills. A qualitative study was conducted among five primary school teachers in the Kapit area of Sarawak, specializing in Malay language. They were selected through purposive sampling to actively participate in this study, bringing their expertise and experiences to enrich the research. The study involved meticulous conduction through semi-structured interviews, and the data were analyzed using thematic analysis with NVivo 12. The results revealed pervasive issues, including i) weak writing skills, ii) poor performance levels, iii) a lack of interest in writing, iv) inadequate language proficiency, v) limited vocabulary, and vi) ineffective idea processing. This study serves as a valuable resource for future researchers by providing insights into the complex challenges faced by non-native speakers in primary school. The identified issues offer a foundation for designing targeted interventions, pedagogical approaches, and curriculum enhancements to improve the writing skills and overall academic performance of non-native speakers.